VEGF-A and PD-L1 Immunoexpression Association with Meningioma Histopathology Grade - Afiati Afiati; Hermin Aminah Usman; Bethy Surjawathy Hernowo; Yunnica Yunnica (Global Medical & Health Communication (GMHC), 2019)
Histopathology grade of meningioma is one of the most common factors determining the prognosis and affects the risk of recurrence and aggressiveness of the tumor. Biological factors related to histopathological grade are vascular endothelial growth factor A (VEGF-A) and programmed death-ligand 1 (PD-L1). This research aimed to understand the association between VEGF-A and PD-L1 with meningioma histopathology grade. This is in vivo research on 60 paraffin blocks of meningioma cases at Dr. Hasan Sadikin General Hospital Bandung from April to November 2018. Paraffin block samples consist of grade I (30), grade II (15), and grade III (15) meningioma. Immunohistochemical staining of VEGF-A and PD-L1 performed to all samples. Data analyzed using the chi-square test with SPSS version 24.0 for Windows. The result shows a significant association between VEGF-A and PD-L1 immunoexpression with meningioma histopathology grade. PD-L1 is the most potent factor that influenced the histopathology grade of meningioma. The study concluded that the histopathology grade of meningiomas influenced by angiogenesis and immune checkpoints. VEGF-A and PD-L1 immunoexpression in meningioma considered as a factor that influences the aggressiveness of meningioma. HUBUNGAN IMUNOEKSPRESI VEGF-A DAN PD-L1 DENGAN DERAJAT HISTOPATOLOGI MENINGIOMADerajat histopatologi meningioma merupakan salah satu faktor yang paling umum menentukan prognosis serta memengaruhi risiko rekurensi dan agresivitas tumor. Faktor biologi yang berhubungan dengan derajat histopatologi adalah vascular endothelial growth factor A (VEGF-A) dan programmed death-ligand 1 (PD-L1). Penelitian ini bertujuan mengetahui hubungan imunoekspresi VEGF-A dan PD-L1 dengan derajat histopatologi meningioma. Penelitian in vivo dilakukan pada 60 blok parafin kasus meningioma di Departemen Patologi Anatomi RSUP Dr. Hasan Sadikin Bandung dari April hingga November 2018. Sampel blok parafin terdiri atas meningioma derajat I (30), derajat II (15), dan derajat III (15). Pulasan imunohistokimia VEGF-A dan PD-L1 dilakukan terhadap semua sampel. Data dianalisis menggunakan uji chi-square dengam SPSS versi 24.0 untuk Windows. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara VEGF-A dan PD-L1 dengan derajat histopatologi meningioma. PD-L1 merupakan faktor paling kuat yang memengaruhi derajat histopatologi meningioma. Simpulan penelitian ini adalah derajat histopatologi meningioma dipengaruhi oleh faktor angiogenesis dan immune check point. Imunoekspresi VEGF-A dan PD-L1 pada meningioma dapat dipertimbangkan sebagai faktor yang memengaruhi agresivitas meningioma.